2016
DOI: 10.1186/s12864-016-3251-8
|View full text |Cite
|
Sign up to set email alerts
|

From yeast to hypha: defining transcriptomic signatures of the morphological switch in the dimorphic fungal pathogen Ophiostoma novo-ulmi

Abstract: BackgroundYeast-to-hypha transition is a major morphological change in fungi. Molecular regulators and pathways that are involved in this process have been extensively studied in model species, including Saccharomyces cerevisiae. The Mitogen-Actived Protein Kinase (MAPK) cascade, for example, is known to be involved in the yeast-to-pseudohypha switch. Yet the conservation of mechanisms regulating such morphological changes in non-model fungi is still poorly understood. Here, we investigate cell remodeling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 103 publications
(141 reference statements)
0
29
2
Order By: Relevance
“…The proximate mechanisms underlying the nutritionally essential induction of yeast-like “ambrosial growth” in ambrosia fungi ( 40 , 41 ) is one of the major open questions in the ambrosia beetle-fungus mutualism. Other Ophiostomatales fungi are known to switch growth form due to environmental stimuli ( 84 86 ), but it is also possible that the OTUs of quorum-sensing bacteria like the Enterobacter or the Stenotrophomonas may act as triggers (see Fig. S30, S31, and S32 at https://doi.org/10.6084/m9.figshare.12477593 ).…”
Section: Discussionmentioning
confidence: 99%
“…The proximate mechanisms underlying the nutritionally essential induction of yeast-like “ambrosial growth” in ambrosia fungi ( 40 , 41 ) is one of the major open questions in the ambrosia beetle-fungus mutualism. Other Ophiostomatales fungi are known to switch growth form due to environmental stimuli ( 84 86 ), but it is also possible that the OTUs of quorum-sensing bacteria like the Enterobacter or the Stenotrophomonas may act as triggers (see Fig. S30, S31, and S32 at https://doi.org/10.6084/m9.figshare.12477593 ).…”
Section: Discussionmentioning
confidence: 99%
“…genomes revealed evidence about the function of some genes such as Cu (encoding the toxin cerato-ulmin, Bowden et al 1994Bowden et al , 1996, Pat1 (encoding a pathogenicity factor, Et-Touil et al 1999), Epg1 (encoding the enzyme endopolygalacturonase, Temple et al 2009) and the presence of DNA transposons (Bouvet et al 2007). More recently, extensive transcriptomic studies using an advanced molecular tool (RNAseq) have identified differential gene expression in the distinct phases of O. novo-ulmi from yeast to hyphae and mycelium Nigg and Bernier 2016).…”
Section: Molecular Advances To Understand the Genetic Clues Behind Elmentioning
confidence: 99%
“…The yeast-to-hypha transition is correlated with the antifungal resistance of C. albicans. As previously reported, cAMP is the key element in triggering hyphal formation [ 1 , 14 , 15 ]. CYR1 and PDE2 regulate a pair of enzymes that are directly responsible for cAMP synthesis and degradation, respectively [ 16 ].…”
Section: Introductionmentioning
confidence: 79%